CHARACTERISTICS PROPERTIES OF PHYSICAL AND MECHANICAL COMPOSITE WOOD POWDER – BAGASSE AS SHIP CONSTRUCTION MATERIAL - Ramdhan, Fajri; Sari, T. Ersti Yulika; Nasution, Polaris (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract The need for wood as the main ingredient in shipbuilding is always increasing and the acquistion of quality wood for construction of shipbuilding is increasingly difficult to find on the market, because this is due to the depletion of wood in the forest. This study aims to determine the physical and mechanical propertiesof wood powder composites and bagasse, so that they can be used as ship construction materials. In making test specimens refer to ASTM and JIS standards. While the physical testing of weight and density refers to the ASTM D970 standard and JIS A5980 water absorption test. Mechanical bending testing refers to the ASTM D790-02 standard, the ASTM D638-08 tensile test and the ASTM D5942-96 impact test. The results showed that the largest water absorption was composite wood powder 60% and bagasse 40% by 13,47%, and the largest density was a composite of wood powder 80% which was 1078,29 kg/m3. The highest bending mechanical test is a composite of wood powder 20% which is equal to 29,689 Mpa which is strongly equivalent to class III wood, the largest tensile test is a composite of wood powder 40% by 25,2547 Mpa which is strongly equivalent to grade V wood, and the biggest impact test is composite 40% wood powder which is 0,0469 J/mm2. Based on the results of the study that composite wood powder and bagasse can be used as construction materials for outer shells and deck houses.Keywords : Wood powder, bagasse, ASTM, JIS, composite, bending, tensile, impact